ANALISIS PENGARUH CITRA MEREK, KESADARAN MEREK, PERSEPSI KUALITAS, DAN LOYALITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPATU ADIDAS (Survei pada Mahasiswa Universitas Slamet Riyadi Surakarta) - Mutiara Widia Pradana Putri, Suprihatmi Sri Wardiningsih & Sunarso (Universitas Slamet Riyadi, 2016)
The objectives of the study were to analyze (1) The influence of brand image toward purchasing decision on Univesity student of Slamet Riyadi Surakarta. (2) The effect of brand awareness toward puchasing decisiom on University student of Slamet Riyadi Surakarta. (3) The effect of quality perception toward purchasing decision on Univesity student of Slamet Riyadi Surakarta. (4) The Effect of brand Loyalty toward purchasing decision on Univesity student of Slamet Riyadi Surakarta. The population in this study were all students of Univesity if Slamet Riyadi Surakarta. The amount of the sample were 120 respondents. Data collection technique for this study was questionnaire after passing through validity and reliability test. The test requirements regression used classic assumption test. The data were analyzed using multiple linear regression test, t-test, F-test, and coefficient determination test. The conclusion of the hypothesis test showed that (1) Brand image does not significantly influence purchasing decision on University student of Slamet Riyadi Surkarta, it was proven from the t-test that the probability value (0,137) is higher than (0,05). (2) Brand awareness does not significantly influence toward purchasing decision on Univesity student of Slamet Riyadi Surakarta, it was proven from the t-test value that 0,190 is higher than 0,05. (3) Quality perception is significantly influenced toward purchasing decision on Univesity student of Slamet Riyadi Surakarta, it was proven by the t-test score that generate a probability value 0,029 < 0,05. (4) Brand Loyalty is significantly influec-ed toward purchasing decision on Univesity student of Slamet Riyadi Surakarta, it was proven by the t-test score that generates a probability value 0,000 < 0,05.Keywords: brand image, brand awareness, perceived quality, brand loyalty and purchasing decisions